Analyse de gros mots dans le film Jeux d’Enfants de Yann Samuell - Juliani, Elisa; Bernadus Wahyudi Joko Santoso; Sri Rejeki Urip; Anastasia Pudjitriherwanti (Universitas Negeri Semarang, 2024)
The study aims to find the forms, referents, functions, then age and gender differences of swearing by the characters in the movie Jeux d'Enfants by Yann Samuell (2003). The data collection method used is the listening method with basic tapping techniques and advanced techniques in the form of free listening techniques and note-taking techniques. The researcher used the commensurate method to analyze the data with the basic technique in the form of the determining element sorting technique with the advanced technique in the form of the comparative linking technique to distinguish. Based on the research results, there are 52 data consisting of 26 nouns, 25 adjectives, and 1 verb. In terms of referents 12 human organs, 8 feces, 4 animals, 6 professions, and 22 mental states. In terms of function, there are 9 expletive functions (self), 20 abusive functions (insults), 2 humorous functions (jokes) and 21 auxiliary (emphasis). In terms of gender, 26 males and 26 females used swear words referring to organs, feces, animals, professions and mental states. In contrast, from age, children, adolescents and adults used swearwords referring to mental states, feces, animals, organs and professions.